The New Invisible College : Science for Development - Wagner, Caroline S. (Book collections on Project MUSE., 2008)
"Combines quantitative data and extensive interviews to map emerging global science networks and trace the dynamics driving their growth. Argues that the shift from big science to global networks creates unprecedented opportunities for developing countries to tap science's potential. Offers a guidebook and playbook for policymakers confronting science's transformation"--Provided by publisher